2013
DOI: 10.1371/journal.pone.0055780
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular Vibration-Sensing Component in Human Olfaction

Abstract: Whether olfaction recognizes odorants by their shape, their molecular vibrations, or both remains an open and controversial question. A convenient way to address it is to test for odor character differences between deuterated and undeuterated odorant isotopomers, since these have identical ground-state conformations but different vibrational modes. In a previous paper (Franco et al. (2011) Proc Natl Acad Sci USA 108:9, 3797-802) we showed that fruit flies can recognize the presence of deuterium in odorants by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
102
2
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(110 citation statements)
references
References 36 publications
2
102
2
4
Order By: Relevance
“…Gane et al (14) have framed the argument for olfactory discrimination of hydrogen isotopomers as one of "shape" vs. "vibration."…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…Gane et al (14) have framed the argument for olfactory discrimination of hydrogen isotopomers as one of "shape" vs. "vibration."…”
Section: Significancementioning
confidence: 99%
“…For example, benzaldehyde is converted to benzoic acid (32), a reaction potentially subject to significant primary isotope effects (2,33,34), which could explain the difference in odor perception for the benzaldehyde isotopomers. Earlier claims that human subjects can distinguish odors of acetophenone isotopomers (9,35) have been shown to be untrue (14,31). Recent studies indicate that Drosophila melanogaster can distinguish acetophenone isotopomers (36,37) and that Apis mellifera L., the honey bee, can be trained to discriminate pairs of isotopomers (38).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…In fact, obtaining a deeper understanding of olfaction, the mechanism for which is still being actively debated, [21][22][23][24][25][26][27][28][29][30] is an important problem in its own right for both fundamental science and industry. [31][32][33][34][35] The prevailing theory, known as the lock-and-key model, explains how the odorant size and shape can provide discrimination in the receptor.…”
Section: Introductionmentioning
confidence: 99%
“…may be possible to distinguish the scents of some very similar odorants, for example between those that are deuterated and non-deuterated. 26,30,37 It was suggested as early as 1938 that the sensing of vibrational spectra of molecules [38][39][40] -later proposed to occur via electron transfer 21,22 -could play an important role in olfaction, supplementing (rather than replacing) the existing lockand-key model. Recent work, focussing on constructing and exploring model systems that capture the important physical processes, 24,27 has shown that this is indeed a viable proposition.…”
Section: Introductionmentioning
confidence: 99%